ANALYSIS OF THE RELATIONSHIP BETWEEN REGION, SEX, AND MARITAL STATUS USING A FOUR-DIMENSIONAL LOG-LINIER IN BENGKULU PROVINCE IN 2022 - Putri Damayanti; Gita Sonia; Novelisa Syendra Wanti; Rada Nur Aisa; Etis Sunandi; Pepi Novianti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tadulako, 2026)
This study analyzes the relationship among four categorical variables age group, gender, marital status, and region of residence among individuals aged 10–24 years in Bengkulu Province in 2022. The analysis employed a four-dimensional log-linear model to examine complex associations between these variables. Data were obtained from the Central Bureau of Statistics (BPS) and organized into a four-way contingency table representing all possible combinations of the observed factors. Model parameters were estimated using the maximum likelihood method, and model fit was assessed using the Pearson Chi-Square test and the Akaike Information Criterion (AIC). The results indicated that models involving only two or three factors did not fit the data adequately. In contrast, the saturated model that included all four factors provided the best fit, with a p-value of 1. These findings suggest that there are strong and complex interactions among age, gender, marital status, and region. Therefore, the relationships among these demographic factors cannot be explained independently but require a comprehensive model that incorporates all interactions.